L-Lysine α-Oxidase: Enzyme with Anticancer Properties - Elena V. Lukasheva; Gulalek Babayeva; Saida Sh. Karshieva; Dmitry D. Zhdanov; Vadim S. Pokrovsky (MDPI AG, 2021)
L-lysine α-oxidase (LO), one of L-amino acid oxidases, deaminates L-lysine with the yield of H2O2, ammonia, and α-keto-ε-aminocaproate. Multiple in vitro and in vivo studies have reported cytotoxic, antitumor, antimetastatic, and antitumor activity of LO. Unlike asparaginase, LO has a dual mechanism of action: depletion of L-lysine and formation of H2O2, both targeting tumor growth. Prominent results were obtained on murine and human tumor models, including human colon cancer xenografts HCT 116, LS174T, and T47D with maximum T/C 12, 37, and 36%, respectively. The data obtained from human cancer xenografts in immunodeficient mice confirm the potential of LO as an agent for colon cancer treatment. In this review, we discuss recently discovered molecular mechanisms of biological action and the potential of LO as anticancer enzyme.